Code-switching practices in a Malaysian multilingual primary classroom from teacher’s and students’ perspectives - Paramesvaran, Malini Devi; Lim, Jia Wei (Indonesian Journal of Applied Linguistics, 2018)
This study investigates a teacher’s and three students’ perspectives on shared instances of code-switching practices in a Malaysian multilingual primary classroom. It seeks to explore and compare whether students perceive the same benefit of code-switching as the teacher does. This bridges the gap of previous studies, which mostly either focused on teachers’ or students’ perspectives on code-switching. Three 11-year-old multilingual students with different levels of English proficiencies and a multilingual teacher were selected as participants for this study. Four hours of English lessons were audio-recorded, and field notes were taken occasionally throughout classroom observations. An individual interview session was conducted with the teacher, and a group interview was conducted with the student participants. The findings showed that the teacher’s code-switching practices helped clear the students’ doubts, reinforced their learning, and encouraged student participation in English lessons. One participant shared the same perspective of code-switching as the teacher did. The other two participants, however, only found it beneficial when the teacher practised code-switching for explanations, especially when constructing simple sentences. Both of these students reported that too much repetition of some words bore them as these were previously learned words. The study concludes that not all the students rely on code-switching to assist them during English lessons.